Memory, History and Resentments in the Primary Public Instruction in the Province of Parana (Brazil, 1853-1889) - Juarez José Tuchinski dos Anjos; Etienne Baldez Louzada Barbosa (Universidade Federal de Santa Maria, 2018)
Dialoging with the historiographic research field on Resentment in History, this work on history of education turns the look towards primary public education in the Province of Paraná, in southern Brazil, in the second half of the nineteenth century, years of 1853-1889. The purpose of this article is to identify some of the resentments that permeated the relationships of those involved with the primary public education in the province of Paraná - provincial presidents, teachers, students, inspectors - and the place that this feeling occupied in life and in educational action of these subjects. The sources questioned are mainly correspondences and offices exchanged between participants in the education of Paraná, and the memorialistic record of Albino José da Silva about the primary school in which he studied. Initially, it is identified the presence of resentment due to the actions and limitations of adults responsible for the organization and implementation of public instruction in the province of Paraná. Then, a similar operation is carried out, but from the personal experiences of the memoirist Albino Silva. In addition to identifying the resentment that the hardness of his childhood awakened in him, it is aimed to observe the reactions that he has produced in his adult life to that feeling.